2009
DOI: 10.1111/j.1467-9566.2008.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Shifting blame/selling health: corporate social responsibility in the age of obesity

Abstract: This paper examines how and why health has become a Corporate Social Responsibility (CSR) strategy for the global food and drink industry (FDI) in the context of current governmental and public calls to address mounting obesity rates. It argues that, despite the current prominence of health within CSR, there has not been a reciprocal interest by those adopting sociological approaches to the study of health and illness in the implications of this strategic uptake of health or in the viability and legitimacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 24 publications
0
74
0
5
Order By: Relevance
“…In the broader sense, corporate social responsibility implies that organizations are part of a larger society, thus accountable to that society for their actions (Kerin et al, 2009;Churchill and Peter, 1995). For example, a study showed that health has become a CSR strategy for the global food and beverage industry in the context of government concern to address increasing obesity rates (Herrick, 2009). Clearly, an organization is responsible to the whole society, including all stakeholders.…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…In the broader sense, corporate social responsibility implies that organizations are part of a larger society, thus accountable to that society for their actions (Kerin et al, 2009;Churchill and Peter, 1995). For example, a study showed that health has become a CSR strategy for the global food and beverage industry in the context of government concern to address increasing obesity rates (Herrick, 2009). Clearly, an organization is responsible to the whole society, including all stakeholders.…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…The literature has previously reported on both Big Food's publicised motivations for undertaking CSR activities (12,13,17) and public health critiques of these strategies (14,26) , but to a much lesser extent on the public perception of these strategies (22,23) . Given that companies argue the social good of CSR activities, and their critics associate them with harm, it is important to gain a better understanding of how the public themselves perceive the strategies and impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies in the critical public health literature also show that Big Food is using CSR to divert public attention away from the negative health effects of its products; avoid government regulation; and shift blame from corporations to consumers (12,13,16,17) . Studies from the critical public health literature have reported that companies use these CSR strategies to build brand image and preferences in an attempt to cultivate a climate in which the consumption of their products is viewed as a natural activity.…”
mentioning
confidence: 99%
See 2 more Smart Citations